PENINGKATAN POTENSI DESA PEKALANGAN MELALUI KEGIATAN SOSIALISASI DAN PELATIHAN JAKABA DEMI MEWUJUDKAN MASYARAKAT YANG KREATIF DAN INOVATIF - Nugrahani, Tri Agustina; Pahlevi, Naufal Reza; Wibowo, Ari Irawan Prasetyo; Pratama, Ferdiansyah Dwi; Henanta, Dinda Alvita Izza; Shinta, Dewi; Kristianti, Meylani; Lutfiah, Diana; Ariani, Dinda Yunistri; Jannah, Fadhila Ilma Thariqul; Agustin, Sindi Dwi; Amalia, Karina Nine (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Jakaba is a type of poc whose main ingredient is water left over from washing rice or commonly called leri water. Jakaba's outreach and training activities carried out in Pekalangan Village were carried out with the aim of increasing village potential. With this activity it is hoped that it can increase the knowledge and income of the community through the utilization of waste water left over from washing rice. This research was conducted using a qualitative descriptive method, and by using interviews and observations to collect the necessary data. The purpose of carrying out the socialization and training of Jakaba's liquid organic fertilizer is community service, namely by increasing farmers' knowledge of Jakaba as a cheap, easy and effective POC with high mineral and nutrient content. Improving the welfare of farmers after developing Jakaba by selling it through social media or marketplaces